Pengembangan Film Animasi 3 Dimensi Peran Kapten Ida Bagus Putu Japa dalam Serangan Umum Kota Denpasar - Adhinta Candra Rima Pratama; I Gede Mahendra Darmawiguna; I Gede Bendesa Subawa (Universitas Pendidikan Ganesha, 2021)
Abstract- The history of the hero's struggle is often not well known by the public, especially regarding the history of the hero's struggle, Captain Ida Bagus Putu Japa. This is due to the lack of sources of information about the stories of the drivers of resistance. Currently, what is known to the public is the Statue of Hero of the Posthumous Captain Ida Bagus Putu Japa at the Niti Mandala Renon roundabout, Denpasar and the heroic values of Captain Ida Bagus Putu Japa are also enshrined and stored by making a diorama in the Bajra Sandhi Museum. With the rapid development of technology, technology is useful for disseminating or disseminating information to the general public. This study aims to develop a 3-dimensional animated film of the role of Captain Ida Bagus Putu Japa in the general attack of Denpasar city. So that with this animated film, it is hoped that the public will know and understand how the struggle of Captain Ida Bagus Putu Japa in defending the city of Denpasar. The research method used in this study is the Multimedia Development Life Cycle method, which has 6 stages, namely concept, design, material collecting, assembly, testing, and distribution. . Based on the results of the test data on the content expert test, the criteria are